2016
DOI: 10.1016/j.molp.2015.12.007
|View full text |Cite
|
Sign up to set email alerts
|

Rice Stomatal Closure Requires Guard Cell Plasma Membrane ATP-Binding Cassette Transporter RCN1/OsABCG5

Abstract: Water stress is one of the major environmental stresses that affect agricultural production worldwide. Water loss from plants occurs primarily through stomatal pores. Here, we report that an Oryza sativa half-size ATP-binding cassette (ABC) subfamily G protein, RCN1/OsABCG5, is involved in stomatal closure mediated by phytohormone abscisic acid (ABA) accumulation in guard cells. We found that the GFP-RCN1/OsABCG5-fusion protein was localized at the plasma membrane in guard cells. The percentage of guard cell p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(33 citation statements)
references
References 33 publications
0
33
0
Order By: Relevance
“…It is probable that 50% of rice crops already experience drought-associated yield losses (Matsuda et al, 2016). Confronted with human population increases, climate change and water scarcity, there is an urgent need to reduce crop water use whilst maintaining photosynthesis, yield and heat tolerance at higher atmospheric CO 2 concentrations (Ainsworth, 2008;Gago et al, 2014;Jagadish et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is probable that 50% of rice crops already experience drought-associated yield losses (Matsuda et al, 2016). Confronted with human population increases, climate change and water scarcity, there is an urgent need to reduce crop water use whilst maintaining photosynthesis, yield and heat tolerance at higher atmospheric CO 2 concentrations (Ainsworth, 2008;Gago et al, 2014;Jagadish et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Rice cultivation is particularly water intensive, using an estimated 2500 l of water per 1 kg of rice produced (Bouman, 2009). However, almost half of the global rice crop derives from rain-fed agricultural systems where incidences of drought and high temperatures are predicted to become more frequent and damaging under climate change (Vikram et al, 2015;Matsuda et al, 2016;Korres et al, 2017). Like most land plants, rice uses microscopic pores called stomata to regulate CO 2 uptake for photosynthesis with the concomitant release of water vapour via transpiration (Zeiger et al, 1987;Murchie et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, up-regulation of stomatal movement genes contributes to drought tolerance. The reduced culm number 1 (rcn1) mutant encoding OsABCG5 shows rapid water loss more than the wildtype plants by deficiency of stomatal closure during drought stress (Matsuda et al, 2016). The rice NAC gene, ONAC022, was also identified as a positive role in drought tolerance through modulating a stomatal closure (Hong et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, 25 genes related to stomatal movement were up-regulated in the OsTF1L OX shoots. These include ATP-BINDING CASSETTE SUBFAMILY G PROTEIN (ABCG5), PECTIN METHYLESTERASE (PME2, 6), Ca 2+ P-TYPE ATPASE (ACA1), VACUOLAR CATION/PROTON EXCHANGER (CAX2), GLUTAMATE RECEPTOR LIKE (GLR1.1) and NAC DOMAIN-CONTAINING PROTEIN (NAC022) (Hong et al, 2016;Matsuda et al, 2016;Pandey et al, 2007; Table S3). We also found that 29 genes involved in lignin biosynthesis are upregulated in the OsTF1L OX shoots.…”
Section: Ostf1l Modulates Drought-inducible Stomatal Movement and LImentioning
confidence: 99%
“…OsABCG5 [ATP‐binding cassette (ABC) subfamily G‐protein], for example, is a GC‐localized protein involved in ABA accumulation in rice GCs in response to drought stress (Matsuda et al , ). Mutants and RNAi lines showed less ABA in GCs upon ABA application and lost more water, which indicates a defect in closing stomata properly (Matsuda et al , ). Similarly, OsPM1 (PM protein 1) is induced by ABA treatment, mediates ABA influx to the GCs in rice and is expressed in GCs but also in vascular tissues and mature embryos (Yao et al , ).…”
Section: Better Faster More Efficient – How An Innovative Morphologmentioning
confidence: 99%